2024
DOI: 10.1088/2752-664x/ad39f2
|View full text |Cite|
|
Sign up to set email alerts
|

Assessing canopy height measurements from ICESat-2 and GEDI orbiting LiDAR across six different biomes with G-LiHT LiDAR

Qiuyan Yu,
Michael G Ryan,
Wenjie Ji
et al.

Abstract: Height of woody plants is a defining characteristic of ecosystems because height responds climate, soil and disturbance. Orbiting LiDAR instruments, ICESat-2 and GEDI, can provide near-global datasets of plant height at high resolution. We evaluate canopy height measurements from ICESat-2 and GEDI with airborne LiDAR in six study sites across different biomes with mean canopy height of 0.5-40 m. ICESat-2 and GEDI provide reliable estimates for the relative height with RMSE and MAE of 7.49 and 4.64 m (ICESat-2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 71 publications
0
1
0
Order By: Relevance
“…Queinnec et al [12] compared the accuracy of ICESat-2 ATL08 forest height measurements in different stand ages, demonstrating that the accuracy is significantly reduced in over-mature stands with complex structure and forest height variability. Existing studies showed that the estimation of forest structural parameters based on ICESat-2 data was strongly reliable, but there was still potential for an improvement in accuracy [16][17][18][19][20][21]. Also, the weak power and diurnal laser signal from ATLAS significantly impacted the accuracy of ICESat-2 products [22].…”
Section: Introductionmentioning
confidence: 99%
“…Queinnec et al [12] compared the accuracy of ICESat-2 ATL08 forest height measurements in different stand ages, demonstrating that the accuracy is significantly reduced in over-mature stands with complex structure and forest height variability. Existing studies showed that the estimation of forest structural parameters based on ICESat-2 data was strongly reliable, but there was still potential for an improvement in accuracy [16][17][18][19][20][21]. Also, the weak power and diurnal laser signal from ATLAS significantly impacted the accuracy of ICESat-2 products [22].…”
Section: Introductionmentioning
confidence: 99%
“…Namely, there is in the first place the basic fact that electromagnetic interactions constituting remote sensing data could not even in theory explain all the variability of forest attributes. And even if this were the case, they would still be susceptible to imperfections in remote sensing input data, whether from lidar sources (Roy et al, 2021;Schleich et al, 2023;Tang et al, 2023;Yu et al, 2024) or imaging sources (Teillet et al, 1982;Joshi et al, 2017;Mutanga et al, 2023), as well as to various modeling choices and parameterizations. Therefore it makes sense that all of these factors combined induce models to fail to spatio-temporally reproduce a substantial part of the variability of the forest attributes.…”
Section: Introductionmentioning
confidence: 99%